NEW ENDOVASAL SURGICAL APPROACHES TO TREAT PURULENT-NECROTIC COMPLICATIONS OF THE DIABETIC FOOT (World Bulletin of Public Health, 2024)
Advances in the diagnosis and treatment of diabetes have led to an increase in the life expectancy of patients, which, in turn, has caused the emergence of a large number of late complications of the disease. At the same time, such formidable complications as heart pathology, renal failure, blindness, and foot lesions develop. Diabetic foot takes a leading position in this list. In the report of the WHO Expert Committee on Diabetes Mellitus, diabetic foot syndrome (DFS) is not considered a manifestation of diabetic angiopathy, but is recognized as an independent disease.
Keywords: Surgical approach; Surgical approachdiabetic foot; diabetes mellitus